2022
DOI: 10.3390/nu14234954
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Cardiovascular Disease Markers in Relation to Serum and Dietary Magnesium in Individuals from the General Population: The KORA-MRI Study

Abstract: Several studies have implied a role of magnesium in the development of cardiovascular disease (CVD). Thus, magnesium might serve as a potential risk marker for early CVD. Therefore, we investigated the association of serum magnesium and dietary magnesium intake with markers of subclinical CVD in a population-based study. We used cross-sectional data from the sub-study of the Cooperative Health Research in the Region of Augsburg (KORA-FF4). Markers of subclinical CVD, namely, left and right ventricular structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…Generally, it is important to note that findings relating to dietary magnesium intake are not directly translatable to findings from serum magnesium levels, since these two parameters do not correlate well. 42 Disturbance in magnesium balance is common in individuals with CKD, primarily due to impaired renal reabsorption, diuretic use, and changes in diet. 43 In fact, Oka et al reported that hypomagnesaemia was the most frequent electrolyte abnormality among 2126 predialysis patients, and positive proteinuria was identified as an independent risk factor for magnesium wasting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, it is important to note that findings relating to dietary magnesium intake are not directly translatable to findings from serum magnesium levels, since these two parameters do not correlate well. 42 Disturbance in magnesium balance is common in individuals with CKD, primarily due to impaired renal reabsorption, diuretic use, and changes in diet. 43 In fact, Oka et al reported that hypomagnesaemia was the most frequent electrolyte abnormality among 2126 predialysis patients, and positive proteinuria was identified as an independent risk factor for magnesium wasting.…”
Section: Discussionmentioning
confidence: 99%
“…These findings may be attributed to the relatively short follow‐up duration and the specific selection of participants. Generally, it is important to note that findings relating to dietary magnesium intake are not directly translatable to findings from serum magnesium levels, since these two parameters do not correlate well 42 …”
Section: Discussionmentioning
confidence: 99%
“…The ABPI is the ratio of the SBP taken at the ankle to that in the arm. An ABPI of 1 is considered normal and an ABPI lower than 0.9 is sign of arterial/venous disease [ 158 ]. The atherosclerosis risk in communities (ARIC) is a prospective epidemiologic study undertaken in four US communities which ran from 1987 to 2013.…”
Section: Effects Of Magnesium Deficiency On the Cardiovascular Systemmentioning
confidence: 99%
“…The incidence of hypoMg in patients with de novo AF admitted to the emergency department and intensive care unit was 8.5% [ 23 ]. Serum and dietary Mg intake were also associated with markers of subclinical CVD and with the presence of various functional and structural parameters of subclinical CVD [ 24 ].…”
mentioning
confidence: 99%